Nutrient Enrichment of Human Milk with Human and Bovine Milk-Based Fortifiers for Infants Born <1250 g: 18-Month Neurodevelopment Follow-Up of a Randomized Clinical Trial. Issue 12 (12th November 2019) - Hopperton, Kathryn E; O'Connor, Deborah L; Bando, Nicole; Conway, Aisling M; Ng, Dawn V Y; Kiss, Alex; Jackson, Jacqueline; Ly, Linh; ,; Unger, Sharon L
ABSTRACT: Background: Bovine milk-based fortifiers (BMBF) have been standard of care for nutrient fortification of feeds for very low birth weight (VLBW) infants, however, there is increasing use of human milk-based fortifiers (HMBF) in neonatal care despite additional costs and limited supporting data. No randomized clinical trial has followed infants fed these fortifiers after initial hospitalization. Objective: To compare neurodevelopment in infants born weighing <1250 g fed maternal milk with supplemental donor milk and either a HMBF or BMBF. Methods: This is a follow-up of a completed pragmatic, triple-blind, parallel group randomized clinical trial conducted in Southern Ontario between August 2014 and March 2016 (NCT02137473) with feeding tolerance as the primary outcome. Infants weighing <1250 g at birth were block randomized by an online third-party service to receive either HMBF ( n  = 64) or BMBF ( n  = 63) added to maternal milk with supplemental donor milk during hospitalization. Neurodevelopment was assessed at 18-mo corrected age using the Bayley Scales of Infant and Toddler Development, Third Edition. Follow-up was completed in October 2017. Results: Of the 127 infants randomized, 109 returned for neurodevelopmental assessment. No statistically significant differences between fortifiers were identified for cognitive composite scores [adjusted mean scores 94.7 in the HMBF group and 95.9 in the BMBF group; fully adjusted mean difference, −1.1 (95% CI: −6.5 to 4.4)], language composite scores [adjusted scores 92.4 in the HMBF group and 93.1 in the BMBF; fully adjusted mean difference, −1.2 (−7.5 to 5.1)], or motor composite scores [adjusted scores 95.6 in the HMBF group and 97.7 in the BMBF; fully adjusted mean difference, −1.1 (−6.3 to 4.2)]. There was no difference in the proportion of participants that died or had neurodevelopmental impairment or disability between groups. Conclusions: Providing HMBF compared with BMBF does not improve neurodevelopmental scores at 18-mo corrected age in infants born <1250 g otherwise fed a human milk diet. This trial was registered at clinicaltrials.gov as NCT02137473.